Dobra vera pri priposestvovanju služnosti - Damjan, Matija (Pravnik, 2015)
The article analyses the possessor's good faith as one of the conditions for acquiring an easement by prescription under the Austrian Civil Code, the Yugoslav Basic Property-Law Relations Act and the Slovenian Property Code. The concept of good faith is discussed as well as the methods of proving or disproving it. A focal question is on what factual basis a possessor acting with due diligence may rely to justify his good faith: a non-registered contract, a state authority's decision or the owner's informal written consent. Since good faith is basically an internal belief that cannot be determined directly, external clues are relevant by which the existence of good faith can be assessed.
Keywords: pogodbe; priposestvovanje; služnostna pravica; stvarne služnosti; zemljiške knjige